Coffee Plants' Endomycorrhizae Potential to increase the growth and nutrient uptake of Arabica Coffee (Coffea arabica L.) under Field Condition - Santi Sariasih; Pingkan Aditiawati (3BIO: Journal of Biological Science, Technology and Management, 2022)
Inorganic fertilizers utilization is the most common way to increase plant productivity. However, the intensive use of organic fertilizer can harm the environment. Therefore, alternative fertilization by utilizing soil microorganisms to provide plant nutrients is needed. Endomycorrhizae is known as a microorganism that can increase the availability of nutrients and plant growth. This study aimed to determine the potential of endomycorrhizae to increase the growth of arabica coffee seedlings under field conditions. A Randomized Complete Block Design (RCBD) with 5 replications was used with four treatments, i.e., (P0) control: without endomycorrhizae and fertilizer, (P1) inorganic fertilizer: NPK recommended dose for seedlings nine months after sowing (N 184 kg/ha, P2O5 72 kg/ha, and K2O 120 kg/ha from 400kg/ha urea, 200 kg/ha SP-36, and 200 kg/ha KCl, respectively), (P2) endomycorrhizae: 1:1 (w/w basis) endomycorrhizal inoculum-planting medium, and (P3) endomycorrhizae + organic fertilizer: 1:1 (w/w basis) endomycorrhizal inoculum-planting medium with the addition of chicken manure at a dose of 10 tons/ha. The results showed that endomycorrhizae could increase the growth of arabica coffee seedlings by increasing plant height, plant dry weight, and plant N, P, and K uptake by 15.4%, 23.3%, 52.5%, 90.8%, and 75.6%, respectively compared to the control with 67,5% of root colonization at 16 weeks after transplanting (WAT). In conclusion, endomycorrhizae can potentially increase the growth of arabica coffee seedlings under field conditions.